2019
DOI: 10.3390/app9214609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specific Parameters on Simulations of Energy Use and Air Temperatures in Offices Equipped with Radiant Heating/Cooling Panels

Abstract: When creating a simulation model to assess the performance of buildings, there is usually a lack of feedback information. Only in the case of measurements of a real building is a direct comparison of the measured values and simulated results possible. Parameter data related to users’ behavior or other events can also be obtained. Their evaluated frequency, magnitude and duration, along with boundary conditions, are crucial for the results. It is clear that none of them can be predicted very accurately. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Papers [1][2][3] are focused on simulation techniques for the evaluation of the energy performance of buildings. For example, Sabina Jordan [1] and her colleagues conducted a parametric study of the influence of the occupant behavior on the energy performance of an office building provided with radiant ceiling panels for heating and cooling. They used TRNSYS, and they concluded that specific human activities influence the annual energy use a small amount and their effects often counteract.…”
Section: Energy Efficiency In Buildings and Innovative Materials For mentioning
confidence: 99%
“…Papers [1][2][3] are focused on simulation techniques for the evaluation of the energy performance of buildings. For example, Sabina Jordan [1] and her colleagues conducted a parametric study of the influence of the occupant behavior on the energy performance of an office building provided with radiant ceiling panels for heating and cooling. They used TRNSYS, and they concluded that specific human activities influence the annual energy use a small amount and their effects often counteract.…”
Section: Energy Efficiency In Buildings and Innovative Materials For mentioning
confidence: 99%